On Management Problem of Energy Use at Medical Institutions in Morocco - М. Ait Bahajou; Т. G. Pospelova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers problems of rational energy use at  medical institutions inMoroccowithin the context of general energy policy and promotion of the ISO 50001:2011 “Energy management systems – Requirements with guidance for use” requirements in one of the largest hospitals of the country.